Nitrated polycyclic aromatic compounds in the atmospheric environment: A review. Issue 11 (3rd June 2021) - Yan, Juping; Wang, Xiaoping; Gong, Ping; Wang, Chuanfei
Abstract: Nitrated polycyclic aromatic compounds (Nitro-PACs) are a class of aromatic compounds with at least one nitro-(NO2 ) functional group on the aromatic ring of polycyclic aromatic hydrocarbons and phenols, including nitrated polycyclic aromatic hydrocarbons (nitro-PAH) and nitrophenols (NPs). Due to their mutagenicity, carcinogenicity and light absorption ability, the emission sources, toxicity, optical properties and radiative forcing effects of nitro-PACs have attracted global attention. In this study, we review the spatial and temporal variation patterns of nitro-PACs worldwide, and highlight the current emission hotspots. The changes in emissions of nitro-PACs under clean energy strategies are compiled, and the optical properties and possible climatic impacts of nitro-PACs are illustrated in detail. Finally, we provide some recommendations for future research, such as further investigation into the determination of nitro-PACs in heavily polluted South Asia and Brazil, the mechanisms of nitro-PACs during photochemical formation and photodegradation processes, the optical properties of nitro-PACs in cloud or fog droplets, and the contribution of nitro-PACs to the total radiative forcing of brown carbon. This review summarizes our understanding of the environmental and climatic effects of nitro-PACs.